2020
DOI: 10.3390/d12020055
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Endophytic Bacteria from Mycorrhizal Tissues of Terrestrial Orchids from Southern Chile

Abstract: Endophytic bacteria are relevant symbionts that contribute to plant growth and development. However, the diversity of bacteria associated with the roots of terrestrial orchids colonizing Andean ecosystems is limited. This study identifies and examines the capabilities of endophytic bacteria associated with peloton-containing roots of six terrestrial orchid species from southern Chile. To achieve our goals, we placed superficially disinfected root fragments harboring pelotons on oatmeal agar (OMA) with no antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 65 publications
0
26
0
1
Order By: Relevance
“…Because of their importance in the survival of these endangered plants, most of the microbiological investigations on orchids have focused on their mycorrhizal associations, leaving aside the potential role of other microbial partners. Bacterial endophytes in orchids have been mainly investigated in commercially valuable species by isolation after surface sterilization of roots and/or leaves, and many isolates have been found to both increase seed germination and promote plant growth ( Tsavkelova et al, 2007 ; Faria et al, 2013 ; da Silva et al, 2015 ; Gontijo et al, 2018 ; Herrera et al, 2020 ). By contrast, culture-independent approaches have been rarely applied to investigate the endophytic bacteria of orchids, and data are only available for the epiphytic orchids Dendrobium officinale and Dendrobium catenatum ( Yu et al, 2013 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their importance in the survival of these endangered plants, most of the microbiological investigations on orchids have focused on their mycorrhizal associations, leaving aside the potential role of other microbial partners. Bacterial endophytes in orchids have been mainly investigated in commercially valuable species by isolation after surface sterilization of roots and/or leaves, and many isolates have been found to both increase seed germination and promote plant growth ( Tsavkelova et al, 2007 ; Faria et al, 2013 ; da Silva et al, 2015 ; Gontijo et al, 2018 ; Herrera et al, 2020 ). By contrast, culture-independent approaches have been rarely applied to investigate the endophytic bacteria of orchids, and data are only available for the epiphytic orchids Dendrobium officinale and Dendrobium catenatum ( Yu et al, 2013 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the strains have been previously reported to be associated with plant growth-promoting activity ( Egamberdieva et al, 2018 ; Afzal et al, 2019 ). For instance, in addition to the well-known plant growth-promoting species of Pseudomonas and Bacillus , Variovorax boronicumulans has been reported to colonize the root tissues of orchids along with mycorrhiza and contribute toward seedling development at early stages ( Herrera et al, 2020 ). The abundance of plant-beneficial bacteria associated with DPF plants might contribute to the survival and establishment of host plants in the natural environment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bacterial endophytes may positively interact to improve the nutrition and growth of mycoheterotrophic species, such as in the case of Arachnitis uniflora and Dendrobium catenatum [39,40]. Associations with such microorganisms are necessary for orchids, especially after the initial mycoheterotrophic stage, for them to become established in the ecosystem [39,41]. Our results showed that, after two months of symbiotic germination, the growing protocorms slow their growth, probably by the lack of appropriated soil-borne fungi able to contribute synergistically to plant growth.…”
Section: Discussionmentioning
confidence: 99%